Male contraception through womens eyes: trust, perceptions and challenges - Mohapatra, Ipsita; Samantaray, Subha Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Contraception has historically been considered a female responsibility, with most contraceptive methods designed for and marketed toward women. There is imbalance in contraceptive responsibility between men and women. Historically, contraception has largely been seen as a woman’s responsibility, with a wide range of options available to them, while men have had only limited choices. This has led to a disproportionate burden on women to prevent unintended pregnancies. Traditional male contraceptive methods, such as condoms and vasectomy, either require consistent use or involve permanent sterilization, leaving men with fewer alternatives. However, advancements in reproductive health are paving the way for new male contraceptive options, including hormonal treatments, reversible vasectomy techniques and non-hormonal methods like sperm-blocking gels. The introduction of these alternatives presents an opportunity to distribute contraceptive responsibility more equally between genders. Women’s perceptions of male contraception play a crucial role in determining its success, as trust, reliability and shared responsibility are central concerns. Many women welcome these new options, seeing them as a way to ease their own contraceptive burden, but concerns over adherence, side effects and effectiveness remain. Society and healthcare providers have a significant role to play in ensuring male contraceptives are widely accepted, properly understood and integrated into reproductive healthcare frameworks. Shifting cultural norms and increasing education on male contraception can help normalize the idea that birth control is not solely a woman’s duty but a shared responsibility between partners. With ongoing research and growing awareness, male contraceptives have the potential to transform the picture of reproductive health, making contraception a more balanced aspect of family planning. As acceptance increases and reliable options become available, the responsibility of preventing unintended pregnancies will no longer rest disproportionately on women, but instead be a mutual commitment between partners, fostering greater equality and cooperation in reproductive decision-making. This article explores historical perspectives, current male contraceptive methods, emerging alternatives, women’s attitudes toward these options, factors influencing trust and the role of society and healthcare providers.